An unorthodox, new endemic species in New Caledonian Marsdenia (Apocynaceae, Asclepiadoideae, Marsdenieae) - Gâteblé, Gildas; Fleurot, Dominique; Meve, Ulrich; Liede-Schumann, Sigrid (Phytotaxa, 2019)
In the course of the writing of the Flore de la Nouvelle-Calédonie treatment for Asclepiadoideae, Periplocoideae and Secamonoideae, several new species have already arisen partly due to more intensive field work and to a renewed interest in this group of plants. In December 2018, another striking and unorthodox new species was spotted and collected on the flanks of the Kopéto massif mining site. Because this new species has morphological characters from three genera (Dischidia, Gymnema and Marsdenia), further studies, especially molecular, were needed to assess its relationships. These studies show it as a member of one of the New Caledonian Marsdenia subclades. We herein propose to describe it as Marsdenia goromotoorum Gâteblé, Fleurot, Meve & Liede, the only species of Marsdenia in New Caledonia lacking both corolline and gynostegial coronas. It is a micro-endemic species with pinkish-red tubular flowers, growing on serpentines and known from only eight plants. Due to the anthropogenic fire threat, we propose to consider it as Critically Endangered.